1977
DOI: 10.1038/hdy.1977.83
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin, aberrant endosperm nuclei and grain shrivelling in wheat-rye genotypes

Abstract: SUMMARYEvidence is presented leading to the conclusion that there is, in wheat-rye genotypes, a causal link first, between the presence of late replicating segments of heterochromatin on rye chromosomes and the occurrence of chromosome bridges at anaphase and of other aberrant nuclei in coenocytie endosperm, and second, between the frequency of occurrence of aberrant nuclei in young endosperms and the degree of grain shrivelling at maturity. Bridges in coenocytic endosperm of wheat-rye genotypes are caused at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 15 publications
2
41
1
2
Order By: Relevance
“…The detrimental influence of rye telomeric heterochromatin on the development of triticale led Bennett (1977) to suggest that the selection of lines containing `modified' rye chromosomes could be beneficial in the breeding of superior lines of this species . An increase in aberrant endosperm nuclei resulting in a corresponding increase in grain shrivelling has been correlated to the amount of telomeric heterochromatin present in the rye genome (Bennett, 1977) ; . It has been recently demonstrated that a loss of approximately 90% of the telomeric heterochromatin from chromosome 6RS of triticale cv .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detrimental influence of rye telomeric heterochromatin on the development of triticale led Bennett (1977) to suggest that the selection of lines containing `modified' rye chromosomes could be beneficial in the breeding of superior lines of this species . An increase in aberrant endosperm nuclei resulting in a corresponding increase in grain shrivelling has been correlated to the amount of telomeric heterochromatin present in the rye genome (Bennett, 1977) ; . It has been recently demonstrated that a loss of approximately 90% of the telomeric heterochromatin from chromosome 6RS of triticale cv .…”
Section: Resultsmentioning
confidence: 99%
“…In genlines of rye (Secale cereale L.) (Lelley et al ., 1978 ; eral, increasing the amount of rye telomeric heter- Giraldez et al ., 1979) . The nature of this variation is ochromatin has a detrimental influence on develstill not understood and continues to attract considopment of the kernel (Merker, 1976 ;Bennett, erable interest . It has recently been demonstrated 1977 ; Bennett & Gus-that the telomeric heterochromatin of rye consists tafson, 1982) .…”
Section: Introductionmentioning
confidence: 99%
“…In triticale cells, the rapid cell cycle of rye may result in insufficient time for chiasmata formation in the chromosomes of wheat (Bennett, 1977). This hypothesis was first suggested with regard to triticale hexaploids by Tsuchiya (1970) and to octoploids by Pieritz (1970).…”
Section: Meiotic Behaviormentioning
confidence: 99%
“…A change in these properties, however, nay be deleterious particularly at certain developmental stages. In triticaie, for example, deleterious effects are seen as shrivelled grains and aberrant endosperm nuclei (Bennett, 1977;. Bennett (1977; and Francis et al (1985) postulate that these effects result from the compliance of the rye chromosomes (S phase of 6.6 hours) to a S phase of 4.7 hours in triticale leaving insufficient time for the replication of late replicating heterochromatin in the rye chromosomes.…”
Section: Replicon Size Fork Rate and S Phase Duration Are Geneticallmentioning
confidence: 99%
“…In triticaie, for example, deleterious effects are seen as shrivelled grains and aberrant endosperm nuclei (Bennett, 1977;. Bennett (1977; and Francis et al (1985) postulate that these effects result from the compliance of the rye chromosomes (S phase of 6.6 hours) to a S phase of 4.7 hours in triticale leaving insufficient time for the replication of late replicating heterochromatin in the rye chromosomes. , 1985), is currently viewed by the authors as a by-product of genomic rearrangements that precede the differentiation of vascular parenchyma cells.…”
Section: Replicon Size Fork Rate and S Phase Duration Are Geneticallmentioning
confidence: 99%